Lagomorpha Characteristics - Argente, María-José; de la Luz García Pardo, María; Dalton, Kevin P. (IntechOpen, 2021)
This book offers an approach to the knowledge of lagomorph characteristics with a focus on Oryctolagus and Lepus genera to which domestic rabbits and hare belong. Specifically, this volume provides an overview of the environmental factors that affect rabbit welfare, like housing systems, thermal and humidity conditions as well as a molecular study of the main viral diseases. Moreover, the book includes a review of the commercial rabbit lines and provides a profitability study for meat production with actual data. In the case of hares, they are threatened in some regions and therefore it is necessary to understand their habitat, morphological and reproductive characteristics, as well as the main infectious diseases that affect them.